Pérolas em chão árido: organização, ação social, ação política e cultura política de mulheres empresárias no estado de Minas Gerais - Maria de Fatima Silva Porto (2007)
This thesis has the main purpose to give visibility to the organization, to the politicaland/or the social actions of the businesswomen in Minas Gerais, from the decade of 1980 until these days, 2006. As we worked with the feminine business category, we were stimulated by the origin of business, the concept of businesswoman (man) and the woman insertion in the Commercial Code. We were also stimulated by the origin and the organization of the state or regional and national business from 1930 to 1945, to next, locates the beginning of the businesswomen organization of Minas Gerais state, whose beginning happened in the 1980s. From these organizations, that is, the national and state business from 1930 to 1945, it was made a comparison of the political practices, in other words, the political culture of those and the business women ategory. Such practices were detected by social and political actions and brought into effect by the feminine business category, what made us search for the meaning of the action, the difference between social and political actions and the conceptualization of private and public sphere, having in mind that such actions are understood from those spheres.For the topic development, we preferred to work with some concepts which constitutethe plot, and the text texture: political subject, public and private spaces, individual andcollective actions, social and political actions, repertoires or political practices, socialresponsibility, moral responsibility, civil responsibility and political culture. Forty five interviews, with some business women who represented the category, were used. The criterion adopted to choose the representative cities, where the interviews were carried out, was the division of the state of Minas Gerais into Planning Regions adopted byThe Brazilian Institute of Geography and Statistics IBGE and João Pinheiro Foundation- FJP, totalizing ten cities. The theoretical basis to work with the concepts was supported by a bibliographical research from a lot of thinkers who supported the text argumentation, referred to throughout this work. The businesswoman, going from the private to the public space, constitutes herself in a political subject, acting, in this last one, in different ways and visions. To this analysis, we 15 tried to distinguish her practices, emphasizing the conceptualization of social and political actions, flowing to a reflection about the distinction of what is civil responsibility from what is moral responsibility, and the presence of civic virtues or republican among the usinesswomen in our study. The insertion of the businesswomen, the search for public space, their participation by means of associations, organizations, entities, club services, ONGs and other public spaces, the practice of social and political actions reflect their political culture that becomes concrete among political subjects in specific spaces. After analyzing the interviews, we verified that a significant number of businesswomen have the political action as practice and most of them have the social action. We can observe that some of them have civil responsibility with republican characteristics. Most of the businesswomen, with the practice of social action, presented civil responsibility and civic virtues as well, but, they were per passed by the moral responsibility, revealing political culture in the businesswomen view. We emphasize that his work makes other probabilities of reflection possible, and it does not put an end to this topic, but, on the other hand, we noticed its amplitude as we tried to know more about it. So far, this research is only one view of many other possible ones.